Molecular surveillance for operationally relevant genetic polymorphisms in Plasmodium falciparum in Southern Chad, 2016–2017 - Das S. (2023)
Background: Resistance to anti-malarials is a serious threat to the efforts to control and eliminate malaria. Surveillance based on simple field protocols with centralized testing to detect molecular markers associated with anti-malarial drug resistance can be used to identify locations where further investigations are needed. Methods: Dried blood spots were collected from 398 patients (age range 5–59 years, 99% male) with Plasmodium falciparum infections detected using rapid diagnostic tests over two rounds of sample collection conducted in 2016 and 2017 in Komé, South-West Chad. Specimens were genotyped using amplicon sequencing or qPCR for validated markers of anti-malarial resistance including partner drugs used in artemisinin-based combination therapy (ACT). Results: No mutations in the pfk13 gene known to be associated with artemisinin resistance were found but a high proportion of parasites carried other mutations, specifically K189T (190/349, 54.4%, 95%CI 49.0–59.8%). Of 331 specimens successfully genotyped for pfmdr1 and pfcrt, 52% (95%CI 46.4–57.5%) carried the NFD-K haplotype, known to be associated with reduced susceptibility to lumefantrine. Only 20 of 336 (6.0%, 95%CI 3.7–9.0%) had parasites with the pfmdr1-N86Y polymorphism associated with increased treatment failures with amodiaquine. Nearly all parasites carried at least one mutation in pfdhfr and/or pfdhps genes but ‘sextuple’ mutations in pfdhfr—pfdhps including pfdhps -A581G were rare (8/336 overall, 2.4%, 95%CI 1.2–4.6%). Only one specimen containing parasites with pfmdr1 gene amplification was detected. Conclusions: These results provide information on the likely high efficacy of artemisinin-based combinations commonly used in Chad, but suggest decreasing levels of sensitivity to lumefantrine and high levels of resistance to sulfadoxine-pyrimethamine used for seasonal malaria chemoprevention and intermittent preventive therapy in pregnancy. A majority of parasites had mutations in the pfk13 gene, none of which are known to be associated with artemisinin resistance. A therapeutic efficacy study needs to be conducted to confirm the efficacy of artemether-lumefantrine.